2014
DOI: 10.1111/1471-0528.13084
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal mortality and morbidity up to 28 days after birth among 743 070 low-risk planned home and hospital births: a cohort study based on three merged national perinatal databases

Abstract: Objective To compare rates of adverse perinatal outcomes between planned home births versus planned hospital births.Design A nationwide cohort study.Setting The Netherlands.Population Low-risk women in midwife-led care at the onset of labour.Methods Analysis of national registration data.Main outcome measures Intrapartum and neonatal death, Apgar scores, and admission to a neonatal intensive care unit (NICU) within 28 days of birth.Results Of the total of 814 979 women, 466 112 had a planned home birth and 276… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
0
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(135 citation statements)
references
References 30 publications
6
111
0
18
Order By: Relevance
“…We compared transport rates to those demonstrated elsewhere in the literature on low‐risk out‐of‐hospital births. Fetal and maternal clinical events that were markers of severe morbidity were identified based on review of the literature and assessment of what could be measured within the BIS or via data linkage to CIHI 2, 5, 7, 12, 23, 24, 25, 26, 27, 28, 29, 30. Specifically for maternal morbidity, we looked for uterine rupture, eclampsia, severe hemorrhage, obstetric shock, obstetric embolism, cerebrovascular event, cardiovascular events, renal failure, fourth‐degree lacerations, sepsis, ventilator support, intensive care unit admission, or transfer to hospital for a nonlabor related event.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared transport rates to those demonstrated elsewhere in the literature on low‐risk out‐of‐hospital births. Fetal and maternal clinical events that were markers of severe morbidity were identified based on review of the literature and assessment of what could be measured within the BIS or via data linkage to CIHI 2, 5, 7, 12, 23, 24, 25, 26, 27, 28, 29, 30. Specifically for maternal morbidity, we looked for uterine rupture, eclampsia, severe hemorrhage, obstetric shock, obstetric embolism, cerebrovascular event, cardiovascular events, renal failure, fourth‐degree lacerations, sepsis, ventilator support, intensive care unit admission, or transfer to hospital for a nonlabor related event.…”
Section: Methodsmentioning
confidence: 99%
“…International literature supports the safety of an out‐of‐hospital birth in a low‐risk population in systems in which an out‐of‐hospital birth is well integrated in a broader maternal‐child health program 2, 3, 4, 5, 6, 7, 8, 9, 10, 11. The safety of a planned home birth under midwifery care in Ontario has been established 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from Europe have shown that out-ofhospital birth can be a safe option for women and their babies when the risk of complications is low. [28][29][30] The European Union defines uniform standards for the education and training of mid-wives, 31 whereas the United States takes a piecemeal approach to the training and credentialing of out-of-hospital birth attendants. The American College of Nurse-Midwives and the North American Registry of Midwives recommend that midwives should at minimum meet the standards of midwifery established by the International Confederation of Midwives (ICM), which include completion of a formal midwifery education program, national certification, and licensure in the local jurisdiction of practice.…”
Section: Discussionmentioning
confidence: 99%
“…İsveç, ABD, Finlandiya, İzlanda, Avustralya ve Norveç gibi ülkelerde ise evde doğum oranları %1'in altın-dadır (Tablo 3). [6][7][8][9][10][11][12][13][14][15][16] AMERİKAN OBSTETRİ VE JİNEKOLOJİ DERNEĞİ KOMİTE GÖRÜŞÜ ACOG'un Şubat 2011 tarih ve 476 sayılı kararı evde doğum uygulamaları ile ilgilidir. 17 ACOG'un planlı evde doğum ile ilgili özet kararları:…”
Section: Geli̇şmi̇ş üLkelerde Planli Ev Doğumlarunclassified